Genus Stathmopoda Herrich-Schäffer, 1853 (Lepidoptera: Stathmopodidae) from China (III): Descriptions of fourteen new species - Wang, Shuxia; Guan, Wei; Wang, Ailing (Zootaxa, 2021)
Fourteen new species of the genus Stathmopoda Herrich-Schäffer, 1853 are described: S. apicihamata S. Wang & Guan, sp. nov., S. sphaeroidea S. Wang & Guan, sp. nov., S. delitescens S. Wang & Guan, sp. nov., S. ferrorufa S. Wang & Guan, sp. nov., S. jinxiuensis S. Wang & Guan, sp. nov., S. laiyangensis S. Wang & Guan, sp. nov., S. miniloba S. Wang & Guan, sp. nov., S. paradiplaspis S. Wang & Guan, sp. nov., S. similignominiosa S. Wang & Guan, sp. nov., S. paraxanthostigma S. Wang & Guan, sp. nov., S. sufusciumeraris S. Wang & Guan, sp. nov., S. trigonia S. Wang & Guan, sp. nov., S. trilobata S. Wang & Guan, sp. nov. and S. xanthostigma S. Wang & Guan, sp. nov.; ten species are newly recorded for China: S. aprica Meyrick, 1913, S. balanarcha Meyrick, 1921, S. callicarpicola Terada, 2012, S. cissota Meyrick, 1913, S. culcitella Sinev, 1995, S. diplaspis (Meyrick, 1887), S. flavescens Kuznetzov, 1984, S. gemmiconsuta Terada, 2012, S. placida Meyrick, 1908 and S. xanthomochla Meyrick, 1913. Images of both adults and genitalia are provided, along with two maps showing the distribution of them in China.